39.0k views
3 votes
PLEASE HELP ME! I REALLY NEED HELP!

PLEASE HELP ME! I REALLY NEED HELP!-example-1

2 Answers

4 votes

Answer:


\bold{161}

Explanation:

We know that
n here is represented by 55 (nth term = 55th term), so we get the 55th term is

-1 + 3(55 - 1)

= -1 + 3(54)

= -1 + 162

= 161

Which is our answer.

User First Zero
by
4.6k points
3 votes

This formula means that a(n) for n, when n is the term number, will give you the term. Meaning, we just have to plug in 55 for n.

a(55) = -1 + 3(55 - 1)

a(55) = -1 + 3 * 54

a(55) = -1 + 162

a(55) = 161

User Legenddaniel
by
4.6k points